TOXICOLOGICAL EFFECT OF INHALED MOSQUITO INCENSE STICKS SMOKE ON THE HISTOLOGY AND BIOCHEMICAL RESPONSES IN EXPERIMENTAL RATS (FUDMA JOURNAL OF SCIENCES, 2020)
This study was carried out to investigate the toxicological effects of four brands of mosquito incense stick smoke (DR insecticide stick (AS-1987), Incense upgraded formula (BM-102), Fragrance (B3-254) and Citronella (A7-435) on selected biochemical and histological profile of male albino wistar rats.  Fifteen (15) wistar rats with mean weight (174.6 Â±0.91g) were randomly divided into five (5) groups. Group I were considered as negative control while group II, III, IV and V were challenged with the brands of mosquito incense stick smoke for 8 hours daily by inhalation for 21 days. Laboratory investigations were carried out using standard protocols. It was observed that the activities of the liver enzymes (Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST) and Alkaline Phosphatase (ALP) increased significantly (p
Keywords: Histopathology; liver enzymes; incense stick based-insecticides; albino wistar rats